Diseño de Propuesta de implementación de energía fotovoltaica en la finca floricultora Kimbaya en El Rosal, Cundinamarca (2023)
In this degree work we studied an alternative for the implementation of renewable energy in the flower industry, given the high energy consumption of the productive sector of cut flowers in Colombia, through a photon collection system with the help of solar panel systems for the use of solar radiation as a renewable resource. Where the case study was carried out in the flower farm Kimbaya, in El Rosal Cundinamarca, so that this sector of the country is where most of the flower industries are located and to study and identify the feasibility and viability of an interconnected system between the photovoltaic and the local network of the municipality. As a result, a viable and implementable proposal was obtained in the farm for the substitution of 17% of alternative energy and having a renewable energy source method that contributes to the reduction of greenhouse gases and climate change, taking care and taking advantage of renewable natural resources.